Value of functional imaging by PET in esophageal cancer - Schmidt, Thomas; Lordick, Florian; Herrmann, Ken; Ott, Katja (Journal of the National Comprehensive Cancer Network, 2015)
In esophageal cancer, functional imaging using PET can provide important additional information beyond standard staging techniques that may eventually lead to therapeutic consequences. The most commonly used tracer is fluorodeoxyglucose (FDG), which has high avidity for both squamous cell cancer and adenocarcinoma of the esophagus. The value of FDG-PET is limited in early esophageal cancer, whereas additional information is provided in 15% to 20% of locally advanced tumors. Neoadjuvant treatment is currently the standard of care in locally advanced esophageal cancer in most countries because randomized studies have shown a significant survival benefit. Because responders and nonresponders have a significantly different prognosis, functional imaging to tailor preoperative treatment would be of interest. Metabolic imaging using FDG-PET is an established method of response evaluation in clinical trials. The value of metabolic response evaluation is known to depend on the histologic subtype and the type of preoperative treatment delivered. An association of FDG-PET-based metabolic response with clinical response and prognosis was shown for absolute standardized uptake value (SUV) or a decrease of SUV levels before, during, and after therapy. However, contradictory findings exist in the literature and prospective validation is missing. Additionally, no consensus exists on time points or cutoff levels for metabolic response evaluation. Furthermore, correct prediction of a posttherapeutic pathologic complete remission is currently not possible using FDG-PET. Of high interest is early response monitoring during preoperative chemotherapy, with potential subsequent therapy modification. This tailored approach still needs validation in prospective multicenter trials.
Gesehen am 06.07.2020